Out At Work : Building a Gay-Labor Alliance - McCreery, Patrick; Krupat, Kitty (Book collections on Project MUSE., 2001)
Although mainstream gay rights organizations have tended to imagine their community as primarily middle class, an overwhelming number of lesbians and gays are working class, and many are already union members. Out at Work identifies the important parallels between the labor and gay rights movements and their shared work of foregrounding human rights, fighting homophobia, and embracing the full range of sexual expression.